Something from nothing : adapted from a Jewish folktale - Gilman, Phoebe (New York : Scholastic Inc, 1992)
Josephs loves the beautiful blanket his grandfather made for him. But when it gets old and ragged his mom wants to throw it away. Luckily Grandpa has an idea. . .
You'll love this wonderful story adapted from a Jewish folktale.
Keywords: Folktale--Jewish; Blankets--Fiction; Resourceful